(untitled) (Research, Society and Development, 2022)
The bulk-fill resin was introduced in dental practice with the aim of reducing the time of clinical procedures, besides offering a better or similar quality compared to conventional composites, in aesthetic direct restorations of posterior teeth. An integrative literature review was carried out based on the following guiding question: "What criteria and advantages should be taken into consideration when choosing the use of bulk fill resins over composite resins in aesthetic direct restorations of posterior teeth?", which was constructed using the PICO strategy. Eight articles were selected for the review, taken from Pubmed and Scielo databases. The aim of this study was to evaluate the use of bulk-fill resins compared to composite resins and their benefits in direct aesthetic restorations of posterior teeth, as well as to analyze the criteria for choosing both materials. It was concluded that bulk-fill resin and composite resin present similar results in direct restorations of posterior teeth. The bulk-fill resin optimizes the time of professionals because it allows a greater increment, but most authors recommend finishing the restorations with conventional composites, due to the risk of postoperative sensitivity that the bulk-fill material presents.